Peran Kader Kesehatan dan Inovasi Olahan Bekatul serta Kombucha Bunga Telang dalam Penanganan Diabetes Mellitus di Desa Dagen, Karanganyar - Wijayanti Wijayanti; Retno Dewi Noviyanti; Dodik Luthfianto; Rusiana Sri Haryanti; Firman Rezaldi (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Diabetes mellitus is one of the non-communicable diseases with a steadily increasing prevalence in Indonesia and can lead to serious complications if not properly managed. Health cadres play an important role in prevention, early detection, and community support to improve the quality of life of patients. Training health cadres is an effective strategy to equip them with knowledge and skills related to diabetes mellitus. In Dagen Village, Karanganyar Regency, ITS PKU Muhammadiyah Surakarta and STIKes Tujuh Belas Karanganyar collaborated to carry out educational activities. The materials provided included the basic concepts of diabetes mellitus, the role of health cadres, balanced nutrition for patients, and the practice of local food innovation. The introduced innovations were food processing using rice bran and fermented butterfly pea kombucha, which are expected to support the health of diabetes patients. The evaluation results showed a significant improvement, with the average pre-test score of 26.3 increasing to 30.15 in the post-test, and 100% of participants showing progress. This proves the effectiveness of the training activities. In conclusion, health cadres have a strategic role as educators, companions, and community mobilizers in managing diabetes. The use of local food ingredients through healthy food innovations can be an applicable solution to support a healthy lifestyle and reduce the risk of complications in diabetes patients, particularly in Dagen Village.